Esquistossomose mansônica na área metropolitana de Belém: a experiência do ambulatório do Núcleo de Medicina Tropical - UFPA - ROJAS, Márcia de Fátima Maciel de (Universidade Federal do Pará, 2013)
Four hundred eight patients with schistosomiasis mansoni were studied. This study was carried out at the ambulatory of the Núcleo de Medicina Tropical/UFPA, in Belem city, during the period from 1997 trough 1999 (retrospectively) and from 2000 trough 2001 (prospectively). Which were divided in two groups: group I, including 105 patients from ambulatory free attendance, and group II including 303 patients tried by Fundacao Nacional de SaUde (FNS), for coproscopic investigation. The statistical analysis showed that there weren't differences between the groups into the variables studied (gender, age, procedence, occupation, educational level, load parasitic eggs, clinic forin and epidemiologic classification's case). So, in both groups we're observed the follow clinical and epidemiological profile: to be between 10 trough 19 years old, male, dwelled in the Telegrafo's district, to have load parasitic eggs, bellow of 200 eggs/g of stool, to be by student, low knowledge's level, and intestinal clinic form. The first of all the risk's factors observed were the worse conditions of residence, precarious basic sanitation, associated the low level economic social and education of population. The area's endemicity is low but it's a public health problem localized into the focal areas, reaching mainly the poor communities and a presented high autochthony. The endemicity low level in spite of migratory continues process and the planorbideos vectors's presence in the region can be justified by the Militant factors to the advanced this endemy, such as rivers's big volume, strong stream and acid pH of their waters.